ANALISIS SWOT PRODUK DEPOSITO PADA PT. BANK MESTIKA DHARMA Tbk CABANG PEMBANTU SETIABUDI - ELSERRA SIEMIN CIAMAS; FLORENCE YONGGO; YULIANA .; DEWI ANGGRAINI; WILLIAM VINCENT (JURNAL ILMIAH KOHESI, 2019)
This study aims to determine the strengths, weaknesses, opportunities and threats (SWOT) at PT. Bank Mestika DharmaTbk. Capem Setiabudi, Medan. The research method used is a descriptive qualitative method. Data is collected throughinterviews and it is analyzed in accordance to the analysis method proposed by Miles and Huberman. The conclusion of theSWOT analysis of deposit products at PT. Bank Mestika Dharma Tbk. Capem Setiabudi. The strength of this companyincludes owning a minimum deposit of Rp 1.000.000,-. and with a low penalty rate, it can attract customers to deposit themoney. The weakness of this company includes interest rates that are less competitive, which is lower than other banks.With a low penalty rate, customers have no difficulty with the 1% penalty unless their deposit amount is large. Theopportunity of this company is to have a promotional activity that opens opportunities for companies to attract the attention ofthe public. The better public view of banking companies and the increasing public awareness of the benefits of savingbecomes a good opportunity for banks. The location is strategic because it is located in the center of the crowd and it alsoprovides opportunities for companies because there is a possibility of being visited by the people around there. And thethreat of this company is about the banking regulations that can change at any time and increasingly become fiercecompetition conditions.